(3eMGSHI GdehGQO GdHTQjI (B:s (3YQV hJMdjd eY eONd HOjd (B/s - (3YHO GdhgGH, Ydj eMeOs; (3YGeQ, SYjO jS s ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 1984)
(3CSS eMGSHI GdehGQO GdHTQjI, eMGSHI GdehGQO GdHTQjI heTcdGJ GdJWHjb, eONd HOjd deMGSHI GdehGQO GdHTQjIs
(3HHdjhZQGajG(B: (3U(B.98s
Keywords: (3EOGQI GdCaQGOs; (3GdeMGSHIs; (3GdehGQO GdHTQjIs